Konsep dasar inflasi: memahami dinamika dan dampaknya terhadap perekonomian indonesia. - mufatihah, fahda ummu (Maliki Interdisciplinary Journal, 2025)
Inflation is an important economic indicator in Indonesia, particularly in the context of developing countries. It reflects not only price changes but also the complex dynamics of demand, supply, and monetary policy. Inflation fluctuations can create market uncertainty, affect investment decisions, and reduce purchasing power. This article discusses the basic concepts of inflation, its types, and its impacts on the Indonesian economy. Understanding inflation enables society to better prepare for ongoing changes. Data shows that the average annual inflation rate in Indonesia over the last decade is 4.16%, reflecting challenges in maintaining price stability. Appropriate monetary policy is crucial for controlling inflation and sustaining economic growth. In conclusion, a deep understanding of inflation and its impacts is necessary for making wise economic decisions and supporting societal welfare.